20 years after the fall of the Berlin Wall: Regional unemployment in Eastern Germany - Uwe Blien; Phan thi Hong Van; Klara Kaufmann; Steffen Kaimer (European Regional Science Association (ERSA), 2010)
20 years after the fall of the Berlin Wall there is still a strong division between the economies and labour markets of eastern and western Germany. In the last few years, however, unemployment has been reduced especially in the East, even in times of economic crisis. Within eastern Germany a strong variation of labour market situations is visible, which has been relatively stable in time. A centre-periphery-structure can be understood by those approaches of regional economics which have the property of path dependency like the New Economic Geography. In the paper the development of unemployment is analysed in a spatial econometrics framework which uses a three-equations background (in the spirit of Elhorst). The results show convergence processes (beta- and sigma-convergence) which are not very strong. An industry structure with an emphasis on manufacturing helps to reduce unemployment. In the analysis spatial autocorrelation is revealed of being significant.
Keywords: 330